Stimulants and First-Onset Tics With ADHD - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2006)
A meta-analysis of studies concerning first-onset tics in children with attention deficit hyperactivity disorder (ADHD) treated with stimulants is reported from the University of Goettingen, Germany.